Rheology and buildability of sustainable cement-based composites containing micro-crystalline cellulose for 3D-printing. (1st December 2019) - Long, Wu-Jian; Tao, Jie-Lin; Lin, Can; Gu, Yu-cun; Mei, Liu; Duan, Hua-Bo; Xing, Feng
Abstract: 3D printing is becoming increasingly popular for construction owing to its reduced environmental impact and lower energy demand than conventional manufacturing. Rapid application of this technology relies largely on the development of high-performance cement-based composites compatible with 3D printers. This study aims to develop high-quality and sustainable cement-based composites containing microcrystalline cellulose (MCC) that can satisfy the requirements for 3D printing. The workability, rheological behavior, buildability, and mechanical properties of the cement-based composites for 3D printing were examined systematically. The rheological analysis revealed that the plastic viscosity and yield stress of mortars with 1 wt% MCC were increased by 20.9% and 190.0%, respectively, compared with those of mortars without MCC. The buildability of mortars with 1 wt% MCC was also improved, and the printed structure exhibited neither large cracks among the printed filaments nor distorted components in the printing process. Compared with the mortars without MCC, the 28-d compressive and flexural strengths of the mortars with 1 wt% MCC were increased by 18.6% and 12.5%, respectively. In addition, the carbon emissions from the overall life cycle of a printed residence were quantified by considering the material attributes of additive manufacturing and using software tools to conduct building information modeling (BIM)-enabled life cycle assessment (LCA) modeling. The results indicated that compared with the mortars without MCC at equivalent mechanical strengths, the mortars containing 1 wt% MCC could reduce the CO2 emissions by 6.82%. The comprehensive improvement in rheological properties and buildability as well as the environmental benefits can promote the sustainable industrial utilization of MCC-reinforced cement-based materials in the 3D-printing industry. Graphical abstract: Image 1 Highlights: 1. Micro-crystalline cellulose (MCC) was evaluated in composites for 3D-printing 2. Printable MCC-reinforced composites exhibited good rheology and buildability 3. BIM and LCA tools were coupled to evaluate the environmental impact 4. Addition of MCC contributed to a reduction in CO2 emissions from the composites 5. High-quality sustainable composites meeting 3D printing requirements were proposed